Iodine Deficiency Disorder and Knowledge about Benefit and Food Source of Iodine among Adolescent Girls in the North Shewa Zone of Amhara Region - Abayneh Birlie Zeru; Mikyas Arega Muluneh; Kassa Ketsela H Giorgis; Mulat Mossie Menalu; Michael Amera Tizazu (Journal of Nutrition and Metabolism)
Background. As the dietary iodine content depends on the iodine contents of the soil where the crop is harvested, in highland areas where the iodine content of topsoil was washed away due to erosion, iodized salt is the main source of iodine. This study assessed the magnitude of iodine deficiency disorder and knowledge about the benefit and food sources of iodine among adolescent girls in the highland areas of the North Shewa Zone, Amhara Region, central Ethiopia. Methods. An institutional cross-sectional study was conducted from October 5, 2018, to December 30, 2019. Through a multistage sampling technique, 625 adolescent school girls were selected from 9 schools. A pretested semistructured self-administered questionnaire was used for data collection. Anthropometric measures and thyroid gland physical examinations were performed by trained nurses. The collected data were entered into the computer through Epi Data 3.1 software, and analysis was performed using Anthro plus and SPSS software. Results. The total goiter rate was 317 (50.7%) with 95%CI of 46.9% to 54.6%. Grade-one and grade-two goiter accounts 226 (36.2%) and 91 (14.6%), respectively. About one-third, 428 (68.5%), had knowledge about locally available iodine source foods and 309 (72.2%) of them mentioned salt as a source of iodine. Over half, 216 (55.1%), of 392 (62.7%) participants who had knowledge about the benefit of iodine knew it prevents goiter. Diet diversity score of <5 food groups [AOR 1.487, 95%CI 1.061–2.083], stunting [AOR 1.876, 95%CI 1.079–3.257], menstruation [AOR 1.615, 95%CI 1.110–2.349], rural residence [AOR 1.412, 95%CI 1.005–1.984], and open salt storage container [AOR 2.001, 95%CI 1.044–3.833] were significantly associated with goiter. Conclusions. Total goiter rate of adolescent school girls is high in the area. Low diet diversity score, stunting, menstruation, rural residence, and using an open container for salt storage increased the risk of goiter. In addition to universal salt iodization, the emphasis has to be given on proper handling and utilization of iodized salts at the household level to avoid iodine deficiency disorder in adolescent girls.